SPECIFIC FEATURES OF TREATING ACUTE HEART FAILURE AND DECOMPENSATED CHRONIC HEART FAILURE IN THE ELDERLY (International journal of medical sciences, 2026)
Numerous studies have shown that data on the treatment of acute heart failure in the elderly are insufficient. Currently, treatment of patients in this age group with decompensated chronic heart failure is based on research findings and expert recommendations. It is known that angiotensin-converting enzyme inhibitors, beta-blockers, mineralocorticoid receptor antagonists, and sodium-glucose cotransporter-2 inhibitors are prescribed for the treatment of decompensated chronic heart failure with reduced left ventricular ejection fraction, regardless of patient age, and their beneficial effects have been proven. However, recommendations and data for the treatment of decompensated chronic heart failure with moderately reduced and preserved left ventricular ejection fraction are insufficient. In recent years, it has been noted that the use of inotropic agents - catecholamines and calcium sensitizers in the treatment of these conditions is appropriate. This article focuses on these classes of drugs.